Dynamic Contrast-Enhanced Magnetic Resonance Imaging of Regional Nodal Metastasis in Nasopharyngeal Carcinoma: Correlation with Nodal Staging. (29th May 2017) - Huang, Bingsheng; Kwong, Dora Lai-Wan; Lai, Vincent; Chan, Queenie; Whitcher, Brandon; Khong, Pek-Lan
Abstract : Objective . To determine if the perfusion parameters by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) of regional nodal metastasis are helpful in characterizing nodal status and to understand the relationship with those of primary tumor of nasopharyngeal carcinoma (NPC). Materials and Methods . Newly diagnosed patients imaged between August 2010 and January 2014 and who were found to have enlarged retropharyngeal/cervical lymph nodes suggestive of nodal disease were recruited. DCE-MRI was performed. Three quantitative parameters, K t r a n s, v e, and k e p, were calculated for the largest node in each patient. Kruskal-Wallis test was used to evaluate the difference in the parameters of the selected nodes of different N stages. Spearman's correlation was used to evaluate the relationship between the DCE-MRI parameters in nodes and in primary tumors. Results . Twenty-six patients (7 females; 25~67 years old) were enrolled. K t r a n s was significantly different among the patients of N stages (N1, n = 3 ; N2, n = 17 ; N3, n = 6 ), P = 0.015 . Median values (range) for N1, N2, and N3 were 0.24 min −1 (0.17~0.26 min −1 ), 0.29 min −1 (0.17~0.46 min −1 ), and 0.46 min −1 (0.29~0.70 min −1 ), respectively. There was no significant correlation between the parameters in nodes and primary tumors. Conclusion . DCE-MRI may play a distinct role in characterizing the metastatic cervical lymph nodes of NPC.